Os caminhos da institucionalização da física experimental em Portugal na segunda metade do século XVIII - Rodrigues, Elton (2008)
The experimental physics in the eighteenth century began its development containing one of the main Cabinets of Physics at the time and a teacher of highlevel, helping to boost the new sciences in the country. Thus, in a first moment, we will approach the beginning of the eighteenth century until the expulsion of the Jesuits, resulting in the creation of the Royal College of Noble and Pombaline Reform. Soon after, we will introduce the changes occurred in the higher education through the statutes of the University of Coimbra and the creation of the Cabinet of Experimental Physics. And finally, we describe some instruments used in the Physical's Cabinet and the work of Giovanni Antonio Dalla Bella, the first lens of experimental physics, which served mainly at the University of Coimbra after the reform of education. This research aims to show that the Experimental Physics, in the second half of the eighteenth century, factors associated with the social, political and cultural, began to consolidate becoming important in the scenary of teaching Portuguese